أثر أنماط القيادة الإدارية على تنمية الإبداع لدى الموارد البشرية – دراسة ميدانية لعينة من المؤسسات الصناعية الخاصة بولاية قسنطينة- - بوجعدار, خالد; دريوش, شهيناز (Sciences humaines; Vol. 32 (2013): SCIENCES HUMAINES)
إن تقدم وازدهار المؤسسات يعتمد على استحواذها على موارد بشرية ذات مهارات فكرية وقدرات إبداعية من جهة، وقادة إداريين متميزين بإمكانهم استثمار هذه القدرات وتوفير الدعم اللازم لها من جهة أخرى؛ من هنا تنبثق إشكالية بحثنا التي تهدف إلى تبيان أثر أنماط القيادة الإدارية على تنمية الإبداع في المؤسسات الصناعية الخاصة بولاية قسنطينة، واقتصرت الدراسة التطبيقية على تبيان أثر النمط القيادي الأوتوقراطي والنمط القيادي الديمقراطي على تنمية الإبداع. ولبحث تلك العلاقة اعتمدنا على منهج المسح بالعينة فشملت الدراسة أربعين ( 40) مؤسسة صناعية خاصة واستخدمنا أداة الاستبيان لجمع البيانات، وتمت معالجة البيانات وتحليلها باستخدام الحزمة الإحصائية (SPSS)  باستخراج التكرارات، النسب المئوية، المتوسطات الحساب   The development and flourishment of companies depend on their possession of human resources endowed with intellectual abilities and creative aptitudes on one hand, and distinguished administrative leaders capable of exploiting and adequately assisting these abilities on the other hand. creativity, from an interactive perspective, is influenced by many factors and variables notably administrative leadership. many different studies have been undertaken to show the effect of this organizational factor on creativity and its development. earlier research was mainly interested in investigating leader's personal characteristics. as the determination of features that might reveal creativity in companies proved difficult, researchers turned their attention to study the leader's behavior and its effect on creativity, which is the main concern of this research. in other words, how  can  the  modes  of  administrative  leadership  affect the development  of  creativity  in   human  resources  in  the private  industrial  companies  of  the  province  of  Constantine? the practical side, however, was limited to show the effect of both the autocratic leadership mode and the democratic one on the development of creativity. from a methodological point of view, this relation was investigated on the basis of the